PERANCANGAN SISTEM INSTRUMENTASI BERBASIS INTERNET OF THINGS PADA ALAT PENDETEKSI BANGKITAN KEJANG PENGIDAP EPILEPSI - Dadan Darmawan; Arnisa Stefanie; Dian Budhi Santoso (Politeknik Harapan Bersama Tegal, 2023)
Epilepsy is a disease caused by chronic neurological disorders which is characterized by recurrent seizures. Many studies have been conducted to try to cure the disease. In fact, medically, epilepsy cannot be cured, but the frequency of seizures can be reduced by taking medicines regularly. Medicines certainly contain chemicals that have negative side effects on the human body. A solution is needed to reduce the long-term effects caused by medicines that reduce the frequency of epileptic seizures. The research entitled